2019
DOI: 10.1111/ffe.13003
|View full text |Cite
|
Sign up to set email alerts
|

Aging effect on combined mode fracture resistance of bitumen

Abstract: Crack growth behaviour of aged and unaged 30/40 asphalt binder at subzero temperature was studied both experimentally and theoretically using a test sample called inclined notched bend beam specimen. A series of fracture tests were conducted on this specimen at two subzero temperatures and different combinations of modes I and II. The fracture toughness of tested asphalt binder was significantly dependent on the aging condition such that the load‐carrying capacity of aged bitumen was up to 60% less than the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…For example, additives such as anti-stripping agent, polyphosphoric acid, Fischer-Tropsch (FT) paraffin wax (Sasobit), crumb rubber, styrene-butadiene-styrene and low-density polyethylene (LDPE) are some of the used additive materials for improving the mechanical and performance characteristics of base bitumen. [44][45][46][47][48][49][50][51][52] These additives are mixed with the binder at a specific temperature and with specific mixing procedure. Then, the F I G U R E 4 Variations of mode I geometry factor for different locations of crack front in the analysed three-dimensional specimens: (a) SCB, (b) ENDB and (c) ENDC.…”
Section: Materials and Fracture Toughness Testingmentioning
confidence: 99%
“…For example, additives such as anti-stripping agent, polyphosphoric acid, Fischer-Tropsch (FT) paraffin wax (Sasobit), crumb rubber, styrene-butadiene-styrene and low-density polyethylene (LDPE) are some of the used additive materials for improving the mechanical and performance characteristics of base bitumen. [44][45][46][47][48][49][50][51][52] These additives are mixed with the binder at a specific temperature and with specific mixing procedure. Then, the F I G U R E 4 Variations of mode I geometry factor for different locations of crack front in the analysed three-dimensional specimens: (a) SCB, (b) ENDB and (c) ENDC.…”
Section: Materials and Fracture Toughness Testingmentioning
confidence: 99%
“…Some test specimens usually in the shape of circular discs including diametral compact-tension (DCT) specimen, [1][2][3][4] centre cracked Brazilian disc specimen, 5 semicircular bend (SCB) specimen, [6][7][8][9][10][11][12][13][14][15][16][17][18][19] edge notch disc bend (ENDB) specimen [20][21][22][23][24][25][26] and edge notch disc diametral compression (ENDC) specimen 27,28 are usually used for conducting the fracture toughness experiments on asphalt mixtures. In addition, beam shape specimens such as rectangular beam specimen containing an edge crack and subjected to three-point bending (TPB) or four-point bending (FPB) [29][30][31][32][33][34][35] or wedge-splitting cube (WSC) 36,37 samples are among the other miscellaneous fracture test specimens employed by the asphalt and bituminous researchers. The above-mentioned test methods were mostly used earlier for performing the pure mode I fracture toughness (K Ic ) experiments on asphalt concrete materials.…”
Section: Introductionmentioning
confidence: 99%
“…A great quantity of research results showed that the brittle fracture characteristic and the crack tip plastic zone of cracked materials under combined mode I-II loading are greatly influenced by the T-stress near the crack tip. 16,[31][32][33][34][35][36] The T-stress, which is the first nonsingular constant term, has been considered to be another important fracture parameter in fracture mechanics, and it has been extensively adopted to improve the prediction accuracy of the conventional fracture criteria. 16,37,38 Some frequently used fracture criteria considering the T-stress are the generalized MTS (GMTS) criterion, 1,14 generalized MERR criterion, 21 generalized SED criterion, 18 extended MTSN criterion 15 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…However, the nonsingular terms of Williams' series expansion as well as SIFs can also play a significant role in the fracture process. A great quantity of research results showed that the brittle fracture characteristic and the crack tip plastic zone of cracked materials under combined mode I–II loading are greatly influenced by the T‐stress near the crack tip 16,31–36 . The T‐stress, which is the first nonsingular constant term, has been considered to be another important fracture parameter in fracture mechanics, and it has been extensively adopted to improve the prediction accuracy of the conventional fracture criteria 16,37,38 .…”
Section: Introductionmentioning
confidence: 99%